The ‘carrot’ and the ‘stick’ to reduce coca plantations in Colombia: An empirical investigation - Hernán Borrero; Jairo Parada (Desarrollo y Sociedad, 2022)
In Colombia, efforts to reduce coca cultivation include forced eradication (FE), interdiction, alternative development (AD), and a series of territorial transformations (TT). Whereas some of these policies have been assessed separately by the empirical literature, no attention has been paid to their possible complementarities. Following an economics of crime approach, we argue that people’s choice to grow coca depends on both the costs imposed by FE and interdiction, on the one hand, and the benefits arising from AD and TT, on the other. To test this, we collect data on the country’s 291 municipalities with net positive levels of coca cultivation from 2005 to 2015 and estimate a panel data regression model with fixed effects. The results suggest that, besides being complementary, these groups of policies also depend on each other to be effective.